2018
DOI: 10.2174/1567205015666180507105326
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Response to Cholinesterase Inhibitors in Alzheimer’s Disease Delays Time to Nursing Home Placement

Abstract: Background: A varying response to cholinesterase inhibitor (ChEI) treatment has been report-ed among patients with Alzheimer’s disease (AD). Whether the individual-specific response directly af-fects time to nursing home placement (NHP) was not investigated.Objective: We examined the relationship between the 6-month response to ChEI and institutionalization.Methods: In a prospective, observational, multicenter study, 881 outpatients with a clinical AD diagnosis and a Mini-Mental State Examination score of 10-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Anti-dementia drugs, particularly acetylcholinesterase inhibitors, were among the most commonly prescribed medications of questionable benefit, a finding which is in line with previous studies [14][15][16]. Acetylcholinesterase inhibitors are indicated for mild to moderate dementia in order to attenuate the manifestation of dementia [30][31][32][33]. However, the indication for acetylcholinesterase inhibitors among nursing home residents with advanced dementia is less clear, and their use in this population is considered off label in Germany [33][34][35][36].…”
Section: Comparison With Other Studiessupporting
confidence: 61%
“…Anti-dementia drugs, particularly acetylcholinesterase inhibitors, were among the most commonly prescribed medications of questionable benefit, a finding which is in line with previous studies [14][15][16]. Acetylcholinesterase inhibitors are indicated for mild to moderate dementia in order to attenuate the manifestation of dementia [30][31][32][33]. However, the indication for acetylcholinesterase inhibitors among nursing home residents with advanced dementia is less clear, and their use in this population is considered off label in Germany [33][34][35][36].…”
Section: Comparison With Other Studiessupporting
confidence: 61%
“…The current pharmaceutical treatment options for Alzheimer disease are still limited to symptomatic interventions by cholinesterase inhibitors (ChEIs) and N -methyl- d -aspartate receptor (NMDA) antagonist memantine, which were both shown to improve functional and cognitive outcomes in a significant percentage of Alzheimer disease patients (Trinh et al ., 2003 ; Howard et al ., 2012 ; Zhu et al ., 2013 ; Dou et al ., 2018 ). Furthermore, studies on Alzheimer disease medication have also reported significant benefits for mortality (Zhu et al ., 2013 ; Black et al ., 2018 ; Mueller et al ., 2018 a ; Pilotto et al ., 2018 ) and a delay in nursing home placement (NHP) (Black et al ., 2018 ; Wattmo et al ., 2018 ) in this patient group. However, until now there have been only very few comprehensive epidemiologic studies investigating the association between the use of Alzheimer disease medications and hospitalisations.…”
Section: Introductionmentioning
confidence: 50%
“…Even though current Alzheimer disease medication use also tended to be associated with lower rates of NHP, in-hospital mortality and mortality after hospitalisation, with the exception of NHP after the third hospitalisation these associations did not reach statistical significance. Although some studies have shown positive effects of Alzheimer disease medication on NHP and mortality (Zhu et al ., 2013 ; Black et al ., 2018 ; Mueller et al ., 2018 a ; Pilotto et al ., 2018 ; Wattmo et al ., 2018 ) none of those studies assessed these outcomes specifically after hospitalisation. A study among PWD hospitalised for pneumonia reported lower in-hospital mortality for PWD receiving donepezil, a ChEI.…”
Section: Discussionmentioning
confidence: 99%
“…Although not RCTs, follow-up of ChEI-treated Alzheimer´s dementia cohorts has shown small cognitive benefits at 2-, 3-and more than 10-years [23][24][25] . Moreover, a positive short-term response to ChEIs can delay nursing home placement 26 . Other studies have shown associations between ChEI-use and decreased risk of myocardial infarction, stroke and death in patients with dementia [27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%